Isolated and Combined Effect of Strength Training and Specific Strength Training on Performance Levels Among Archers - Arun Kumar Chatla; K Venkata Narasimha Rao; Deepak Pandey; Laishram Shila Devi; Vaddepalley Satyanarayana (OVS LLC, 2023)
Study purpose. The purpose of the study was to find out the impact of isolated and combined effect of Specific Strength Training, Strength Training, and Combined Strength Training on the performance levels among archers. Materials and methods. Quantitative research study and non-random sampling method used for the study, a total of sixty (N=60) archers from various archery academies across India aged between 20.5±3.8 years were divided into four groups - Control Group (CG), Specific Strength Training Group (SSTG), Strength Training Group (STG) and Combined Strength Training Group (CTG) received 12 weeks of training schedule. SSTG & STG received alternate days/week where as CTG received alternate days of strength and specific training schedule. Results. The results of the data were analysed using Analysis of Covariance (ANCOVA) followed by Bonferroni post hoc test and showed that the implementation of training methods significantly impacted the scoring performance index among the archer groups (SST<0.05, ST<0.05 and CT<0.05). The combined training group achieved highest performance index following strength training and specific strength training. However, no significant improvement in scoring performance index was found in the control group. Conclusions. This research is an evidence that combination of training with shooting is necessary for improving the performance index among archers.